Placenta and Umbilical Cord Cause in Antepartum Deaths - Mantakas, Xenofon (Cureus, 2018)
Stillbirth is a sudden and painful event for parents and obstetrical specialists as well. It is, therefore, of greatest importance to be able to give answers for the cause in order to plan a subsequent pregnancy. The aim of this retrospective study is to estimate the placental and umbilical cord cause of intrauterine death in relation to different gestational ages. The study took place on the Medical Birth Registry of Aretaieio Hospital, National and Kapodistrian University, Athens, Greece. We include a total of 19,283 pregnancies from 1998 to 2012. In this study period, 431 embryonic deaths occurred. The clinical history was documented on admission at delivery. Conditions thought to be associated with the intrauterine fetal death were recorded. Gestational age was calculated from the last menstrual period as well as with the three-trimester system. The autopsy, placenta and umbilical cord examination were performed by the same laboratory of pathology in Aretaieio University Hospital. We found that the majority of stillbirths occurred in the second trimester. We examined placenta and umbilical cord in all cases. The most frequent histologic abnormalities were those indicated placental vascular insufficiency. As far as the umbilical cord is concerned we found that the inflammatory disorder was the most common in antepartum deaths. A single umbilical artery was significantly related to gestational diabetes and congenital embryonic anomalies. Finally, our results showed steady declines in antepartum deaths during 1998-2012. As a result, we reached the conclusion that in order to reduce the fetal death rate, we have to insist on the autopsy of the placenta and umbilical cord in order to gain the appropriate information in counseling the parents.